(untitled) (AmeriQuests, 2012)
Given the diasporic origins of the overwhelming majority of their populace, most countries in the Americas have had to indigenize themselves. Some of them have been content to simply “play Indian.” However, many others have attempted to achieve national legitimacy by fusing their Indigenous and non-Indigenous inhabitants, even if they subsequently do not always admit it. In this essay, I examine how two foundational inter-American novels, José de Alencar’s Iracema and Howard O’Hagan’s Tay John, convey the contrasting ways in which Brazil and Canada have used racial hybridity in their national imaginaries; the former by celebrating the union of the Indigenous and the European that culminates in the birth of the first Brazilian, and thus the Brazilian nation; the latter, which is set in the aftermath of the fall of Batoche and the end of the Métis national dream, by dramatizing the apparent impossibility of racial mixing in Canada. Tellingly, despite the fact one country has embraced what one might term an ideology of ethnoracial hybridity and the other has largely rejected it, both of them have been culturally and politically dominated by groups of European descent. No less important, Indigenous people seem to have become more prominent in the country that historically has been uncomfortable with ethnoracial hybridity, Canada, than with the one that ostensibly glories in it, Brazil.